Corruption, democracy, and economic growth in Kenya - Mose, Naftaly (Asian Journal of Economics and Empirical Research, 2025)
The relationship between corruption, democracy, and economic growth is complex and multifaceted across empirical studies. Understanding this relationship is crucial for policymakers, researchers, and scholars alike as they seek to promote stable democracies and sustained economic development in middle-income countries. Kenya has long grappled with issues of corruption and challenges to its democratic processes. These problems have significant implications for governance, economic growth, political stability, religion, and social cohesion. This study investigates the effects of democracy and corruption control on Kenya’s economic growth from 1990 to 2020. Utilizing the generalized method of moments (GMM) model for regression econometric analysis, the findings indicate that both democracy and control of corruption exert a positive and significant influence on economic growth in Kenya. The results of the democracy model support a positive correlation between democratic governance and economic development, while the corruption model aligns with the “sand in the wheels” hypothesis, suggesting that corruption may hinder economic growth in Kenya. Consequently, advancing democracy, streamlining bureaucratic processes, and implementing anti-corruption measures are crucial for achieving sustainable economic growth in Kenya. Ultimately, promoting good governance and transparency is essential for sustainable economic development, as strong democratic institutions can help mitigate corruption and enhance economic growth potential.